2015
DOI: 10.1186/s13063-015-0822-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the efficacy of EVICEL™ on blood loss in orthopaedic surgery after total knee replacement: study protocol for a randomised controlled trial

Abstract: BackgroundAfter total knee replacement, overall blood loss is often underestimated, although it exceeds the visible blood loss caused by bleeding into the tissues or into the joint. The use of fibrin sealants during surgery has been suggested to reduce perioperative blood loss and transfusion rates and may be beneficial for patient recovery and the postoperative function of the joint.Methods/DesignThis will be a single-centre, single-blinded, randomised controlled trial with a parallel design, for which 68 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However,it is still unclear that if HBL would compromise postoperative knee function. Budde et al found better knee function in patients with less intra-and postoperative blood loss [22]. They compared 34 patients undergoing standard TKA with 34 patients receiving a kind of hemostatic after TKA, and found a better function outcome in the hemostatic group.…”
Section: Discussionmentioning
confidence: 99%
“…However,it is still unclear that if HBL would compromise postoperative knee function. Budde et al found better knee function in patients with less intra-and postoperative blood loss [22]. They compared 34 patients undergoing standard TKA with 34 patients receiving a kind of hemostatic after TKA, and found a better function outcome in the hemostatic group.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1972, the adjunctive use of fibrin sealants in certain surgical procedures has been adopted as an optional approach to manage hemostasis and minimize blood loss after surgical interventions. Nevertheless, the efficacy of fibrin sealants in TKA surgery has not yet attained the status of a standard practice [12]. Review articles and meta-analysis reports have indicated that high-dosage fibrin sealant is effective and safe as a hemostatic therapy for patients undergoing TKA [13][14][15].…”
Section: Introductionmentioning
confidence: 99%